New overall equipment effectiveness framework development with integration of maynard operation sequence technique for losses visualization - Yoong, Sai Sieng (UTeM, 2018)
Overall Equipment Effectiveness (OEE) is a performance indicator used to monitor the performance of the machine and identify the scope of improvement. It is a combination of the three main factors, availability, performance and quality. However, there are losses invisible in the OEE scale due to the low visibility. This will cause the optimization of the machine performance hardly achieved. To overcome the issue, modification needs to be done to visualize the losses in a better way. The aim of this study is to develop a new modified OEE framework to visualize the losses in a better way. This can be achieved through three objectives. The first objective is to investigate the integration of the OEE with other tools and modification of the OEE calculation. Second objective is to develop a new OEE framework to integrate MOST into OEE calculation. Third objective is to evaluate the effectiveness of new OEE framework in visualise losses by comparing with general OEE. Literature review is done on the integration of the OEE with other tools and also the modification that has been done on the OEE. It showed the integration of the OEE and modification on the OEE are based on the specific requirements or purposes. Next, two new equations, usability and human factor are developed to integrate the MOST into the OEE calculation. The usability is used to quantify the frequency of the setup and changeover process and human factor is indicates the human losses that occupy the available time of the machine. Finally, new modified OEE level and general OEE level are calculated by the real data taken from a wire bond machine in the studied company. The data is taken for 35 days. The outcome of the study shows the new modified OEE able to visualize the losses and show the area of improvement. Although the OEE level is same for both OEE calculations but the new modified OEE quantify the losses in a better visualization. It is beneficial for the user to identify the area of improvement correctly and monitor the losses easily. It is expected to implement in various kinds of industry to evaluate the application of the new modified OEE.